Analisis Ketangguhan Pada Istri Narapidana (Studi di Kemukiman Garot Kecamtan Indrajaya Kabupaten Pidie) - Miftahul Jannah; Zulyadi Teuku (Program Studi Kesejahteraan Sosial Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Islam Negeri Ar-Raniry, 2023)
A prisoner's wife is the legal status of husband and wife according to the law for a woman who is the married partner of a prisoner. The wife who was supposed to be the backbone has now become the backbone because of the circumstances that befell her household. This problem is not an easy thing for a prisoner's wife to face. The aim of the researcher is to find out the indicators of toughness of a prisoner's wife and the implications of the toughness of a prisoner's wife for the survival of her family members. This research uses a qualitative research method with a descriptive approach. Data collection was carried out through interviews, documentation and observation. The results of the research show that the toughness indicators of prisoners' wives have a high ability to survive due to the informants having the characteristics of emotional regulation, optimism, impulse control, self-efficacy, causal analysis, empathy and reaching out. By having these tough characteristics, convict wives can maintain their households. The implication of the toughness possessed by prisoners' wives is that they can survive in the household and be able to educate their children even without their husbands. Based on the description above, the prisoner's wife has a strong personality in carrying out her life.